Qira’at Mutawātir dalam Jāmi’al-Bayān fī Ta’wiīl Al-Qur’ān - Ahmad Hawasi (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2019)
Aṭ-Ṭabari is one of the commentators who is concerned about the various readings contained in the Al-Qur'an. The methodology adopted by him in describing the qira'at was by mentioning the various readings, then the implications in meaning and interpretation, then he tarjīḥ from some of these reading methods. However, in doing tarjīḥ, aṭ-Ṭabari did not get a positive response from qira'at scholars such as as-Sakhawi, Labib Sa'id and others, because it seemed as if aṭ-Ṭabari had done a lot of courage by means of mentarjīḥ qira'at. mutawātir sourced from the Messenger of Allah. There are several arguments that are used as aṭ-Ṭabari in mentarjīḥ qira'at, in this case qira'at mutawātir. The author notes that there are three reasons used by him, namely: First, the linguistic aspect (lughah). Second, the grammatical aspect of the language (nahwu). Third, aspects of the standard way of writing (rasm al-muṣḥaf al-imām)